Гармонізація оподаткування прибутку підприємств в ЄС: досвід для України - Вієцька, О.В. (Економіка промисловості, 2015)
Досліджено процес гармонізації оподаткування прибутку підприємств в ЄС. Визначено переваги та недоліки впровадження СССТВ. Обґрунтовано можливі наслідки гармонізації ставки податку на прибуток та бази оподаткування податком на прибуток підприємств для країн старих та нових членів Європейського союзу з урахуванням особливостей розвитку національних економік. Обґрунтовано неможливість повномасштабного включення України у процес гармонізації оподаткування прибутку підприємств в ЄС. Исследован процесс гармонизации налогообложения прибыли предприятий в ЕС. Определены преимущества и недостатки внедрения СССТВ. Обоснованы возможные последствия гармонизации ставки налога на прибыль и базы налогообложения налогом на прибыль предприятий для стран старых и новых членов Европейского союза с учетом особенностей развития национальных экономик. Обоснована невозможность полномасштабного включения Украины в процесс гармонизации налогообложения прибыли предприятий в ЕС. The process of harmonization of corporate income taxation in European Union is investigated in the article. The stages of acceptance of СССТВ are distinguished. Advantages and disadvantages of СССТВ from the position of separate member‟s states of European Union are set. The possible consequences of harmonization of corporate income taxation in European Union are divided on three directions: formula of income distribution, corporate income tax rate, and corporate income tax base. It is set that the old and new member states of European Union can have different consequences of corporate income taxation in European Union by virtue of different features of national economies. Size of economy, requirement in a capital, tax culture and moral, system of personal income taxation, accounting model, rates of GDP, and rates of inflation are considered to be the basic influencing factors. It is reasonable that distinctions in these factors require the different model for the construction of corporate income taxation. Thus, the new member states of European Union can suffer both from introduction of corporate income tax rate and corporate income tax base. It was grounded that full-scale including of Ukraine in the process of harmonization of corporate income taxation in European Union is impossible. It is related to the condition of Ukrainian economy. All analyzable factors fall behind from the new member states of European Union, and even more - from the old member states of European Union. Moreover, the aim of old member states of European Union is the maintenance of high standards, and new member states of European Union - bringing in foreign investments, and the aim of Ukraine is the solution of issue of fiscal deficit. All this requires the different model on the construction of corporate income taxation.